Improving the tournament performance of ATP players from the perspective of efficiency enhancement - Tsai, C.-H.; Yeh, D.-Y.; Chang, C.-C. (International Journal of Sports Science, 2014)
This study analysed efficiency changes in the intertemporal tournament performance of tennis players in the Association of Tennis Professionals (ATP) and proposed improvement suggestions to assist these players in improving their tournament performance from the perspective of efficiency enhancement. Nine tournament performance indices were used to evaluate the data collected from 45 ATP players between 2007 and 2010. Data envelopment analysis approach and Malmquist production index were adopted to determine efficiency measures. We used a strategic management map to locate the players in various characteristic groups according to their efficiency measures and provided inefficient players with a distinctive proposal for improving their tournament performance. The proposal had the characteristics of benchmarking learning, hierarchy (including macro-level and micro-level) and customization (for each inefficient ATP player).